2019
DOI: 10.1101/783050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A functional cortical network for sensorimotor sequence generation

Abstract: The brain generates complex sequences of movements that can be flexibly reconfigured in real-time based on sensory feedback, but how this occurs is not fully understood. We developed a novel 'sequence licking' task in which mice directed their tongue to a target that moved through a series of locations. Mice could rapidly reconfigure the sequence online based on tactile feedback. Closed-loop optogenetics and electrophysiology revealed that tongue/jaw regions of somatosensory (S1TJ) and motor (M1TJ) cortex enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…Anterior lateral motor cortex (ALM) is a critical node in a decision-making circuit that controls directional-licking in response to sensory inputs (8,11,13,14,22,23). To study sensorimotor transformations in this circuit, we developed a delayed-response task, in which mice learned to respond by directional licking to optogenetic stimulation of genetically defined neurons in layer 4 of vibrissal somatosensory cortex (vS1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anterior lateral motor cortex (ALM) is a critical node in a decision-making circuit that controls directional-licking in response to sensory inputs (8,11,13,14,22,23). To study sensorimotor transformations in this circuit, we developed a delayed-response task, in which mice learned to respond by directional licking to optogenetic stimulation of genetically defined neurons in layer 4 of vibrissal somatosensory cortex (vS1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activities along GD and CDgo change rapidly after the Go cue (latencies, 20.0 (16-24) ms, 30.4 (18-44) ms, respectively; mean (2.5-97.5% confidence interval); Methods; Figure 1G) preceding movement onset (64.3 (56-75) ms; mean (2.5-97.5% confidence interval); blue dashed line in Figure 1G). Because activities along GD and CDgo precede movement (Figure S1J), and because silencing of ALM results in loss of behavioral responses (Komiyama et al, 2010;Gao et al, 2018;Xu et al, 2019), we hypothesized that activity along CDgo is the motor command as it is movement-type selective, whereas activity along GD switches the dynamics by terminating CDdelay and triggering CDgo.…”
Section: A Mode Switch Before Movement Initiationmentioning
confidence: 99%
“…movement direction or target; eye, tongue, arm or orienting movements) and a Go cue after a delay instructs movement onset: the Go cue releases planned actions. The anterior lateral motor cortex (ALM), a part of MCx, is necessary for motor planning and execution of directional licking in mice (Komiyama et al, 2010;Guo et al, 2014;Gao et al, 2018;Xu et al, 2019). Stimulation of ALM triggers rhythmic licking.…”
Section: Introductionmentioning
confidence: 99%
“…(C) Probability of grooming or grooming-related movements in ChR2 mice (N=9) was significantly greater than in EYFP mice (N=6) at the onset of the laser pulse (two-way repeated measures ANOVA, significant time x virus interaction, significant in bins 1-3.5s after laser onset). (D) Reliability of evoking a grooming response was calculated by dividing the number of trials in which an animal started grooming or performing grooming movement fragments during laser-on time by the total number of trials (51). ChR2 mice had significantly greater reliability of an evoked response (47%) relative to EYFP mice (0.13%) (t-test, p=.01).…”
Section: Optogenetic Stimulation Of Cs Evokes Partial Grooming Movementsmentioning
confidence: 99%
“…Burguiere and colleagues also showed that activating LOFC inputs to CS was sufficient to reduce this grooming behavior, suggesting that LOFC serves as an inhibitor of abnormal behavior generated in CS (Burguiere et al, 2013). However, CS inputs from ALM, a region that has been associated with preparation, sustainment, and sequencing of trained behavior (Guo et al, 2014;Li et al, 2015;Rothwell et al, 2015;Xu et al, 2019), have not yet been examined. We therefore sought to determine whether CS and its inputs from ALM mediate spontaneous naturalistic behavior.…”
Section: Introductionmentioning
confidence: 99%